Threonyl-tRNA Synthetase Promotes T Helper Type 1 Cell Responses by Inducing Dendritic Cell Maturation and IL-12 Production via an NF-κB Pathway - Jung, Hak-Jun; Park, Su-Ho; Cho, Kyung-Min; Jung, Kwang Il; Cho, Daeho; Kim, Tae Sung (Frontiers in Immunology, 2020)
Threonyl-tRNA synthetase (TRS) is an aminoacyl-tRNA synthetase that catalyzes the aminoacylation of tRNA by transferring threonine. In addition to an essential role in translation, TRS was extracellularly detected in autoimmune diseases and also exhibited pro-angiogenetic activity. TRS is reported to be secreted into the extracellular space when vascular endothelial cells encounter tumor necrosis factor-α. As T helper (Th) type 1 response and IFN-γ levels are associated with autoimmunity and angiogenesis, in this study, we investigated the effects of TRS on dendritic cell (DC) activation and CD4 T cell polarization. TRS-treated DCs exhibited up-regulated expression of activation-related cell-surface molecules, including CD40, CD80, CD86 and MHC class II. Treatment of DCs with TRS resulted in a significant increase of IL-12 production. TRS triggered nuclear translocation of the NF-κB p65 subunit along with the degradation of IκB proteins and the phosphorylation of MAPKs in DCs. Additionally, MAPK inhibitors markedly recovered the degradation of IκB proteins and the increased IL-12 production in TRS-treated DCs, suggesting the involvement of MAPKs as the upstream regulators of NF-κB in TRS-induced DC maturation and activation. Importantly, TRS-stimulated DCs significantly increased the populations of IFN-γ+CD4 T cells, and the levels of IFN-γ when co-cultured with CD4+ T cells. The addition of a neutralizing anti-IL-12 mAb to the cell cultures of TRS-treated DCs and CD4+ T cells resulted in decreased IFN-γ production, indicating that TRS-stimulated DCs may enhance the Th1 response through DC-derived IL-12. Injection of OT-II mice with OVA-pulsed, TRS-treated DCs also enhanced Ag-specific Th1 responses in vivo. Importantly, injection with TRS-treated DC exhibited increased populations of IFN-γ+-CD4+ and -CD8+ T cells as well as secretion level of IFN-γ, resulting in viral clearance and increased survival periods in mice infected with influenza A virus (IAV), as the Th1 response is associated with the enhanced cellular immunity, including anti-viral activity. Taken together, these results indicate that TRS promotes the maturation and activation of DCs, DC-mediated Th1 responses, and anti-viral effect on IAV infection.